How childhood stunting reduced in Gujarat: An analysis of change between 1992 and 2016 - Avula, Rasmi; Menon, Purnima; Nguyen, Phuong Hong; Mani, Sneha S.; Kohli, Neha; George, Nitya; Kanani, Shubhada (International Food Policy Research Institute, 2021)
India comprises one-sixth of the world’s population and one-third of the global burden of undernutrition. Between 2006 and 2016, India made progress in reducing stunting among children below five years; the progress, however, was not uniform across all its states (Menon et al. 2018). There are interstate differences in stunting reduction despite a common national framework for nutrition-specific and nutrition-sensitive programs. Given the paucity of insights on what factors drive successful change in nutritional outcomes such as stunting at the state level in India, we conducted studies in the four states of Chhattisgarh, Gujarat, Odisha, and Tamil Nadu. In this report, we present an analysis of the change in stunting among children less than five years of age over a 24-year period in the state of Gujarat in India. We chose to study Gujarat—along with the states of Odisha (Kohli et al. 2017) and Chhattisgarh (Kohli et al. 2020)— because between 2006 and 2016, declines in stunting in these states, in absolute terms, were higher than the national average.